Long-Term Video Electroencephalography and Electrocorticography in Temporal Lobe Epilepsy-Related Surgery - Xiang, J.; Jiang, Yu. (Нейрофизиология, 2015)
Eighty-eight patients suffering from temporal lobe epilepsy (TLE) underwent epilepsy-related surgery monitored by preoperative long-term video EEG (VEEG) and intraoperative ECoG. The patterns, location, and spatial distribution of epileptiform discharges recorded by VEEG and ECoG were analyzed and compared. In 56 patients, frequent focal epileptiform discharges were recorded by VEEG at one side of the temporal lobe and identified in the temporal lobe and interior frontal gyrus by ECoG. Epileptiform discharges were recorded by VEEG at both sides of the temporal lobe in 20 patients and by all recording electrodes at one side of the temporal lobe in 12 patients. In these patients, epileptiform discharges were identified by ECoG in the left sylvian gyrus of the temporal lobe and in the inferior and middle frontal gyri. Spatial distributions of epileptiform discharges were adequately identified by ECoG in 52 (59%) patients, with a consistency of > 80% in 24 (27%) patients, and with a consistency of 60-80% in 12 (14%) patients, compared with that estimated by VEEG. Patients remained seizure-free in 72 (81.8%) cases; their state was improved significantly in 12 (13.6%) cases and remained unimproved in 4 (4.5%) cases. Our data suggest that ECoG possesses certain advantages over VEEG in accurate localization of the epileptogenic foci and, thus, is important for surgical treatment of TLE. У перебігу хірургічного лікування 88 пацієнтів з темпоральною епілепсією (ТЕ) використовували тривалу преопераційну відеоелектроенцефалографію (ВЕЕГ) та інтраоперативну електрокортикографію (ЕКоГ). Аналізували патерни, локалізацію і просторовий розподіл епілептиформних розрядів, та порівнювали результати використання ВЕЕГ та ЕКоГ. Фокальні епілептиформні розряди, що виникали з великою частотою, були зареєстровані за допомогою ВЕЕГ у 56 пацієнтів унілатерально в темпоральній частці кори, а ЕКоГ дозволяла ідентифікувати такі розряди в темпоральній частці та нижній фронтальній звивині. Подібні розряди відводилися від обох темпоральних часток у 20 пацієнтів та всіма електродами унілатерально від однієї темпоральної частки у 12 пацієнтів. У цих пацієнтів епілептиформні розлади ідентифікувалися за допомогою ЕКоГ у лівій сільвієвій звивині темпоральної частки та в нижній і середній фронтальних звивинах. Просторовий розподіл епілептиформних розрядів був адекватно ідентифікований за допомогою ЕКоГ у 52 (59 %) пацієнтів; співпадіння з даними ВЕЕГ складало більше 80 % у 24 (27 %) пацієнтів і було в межах 60–80 % у 12 (14 %). Судоми були усунуті у 72 (81.8 %) пацієнтів; стан хворих був істотно поліпшений у 12 (13.6 %) випадках і не змінювався у чотирьох (4.5 %) випадках. Наші дані свідчать про помітні переваги ЕКоГ над ВЕЕГ в аспекті можливості визначення точної локалізації епілептогенних фокусів, і, таким чином, її застосування є доцільним при хірургічному лікуванні ТЕ.